Performance analysis on the safety and automation system of a modified cutting machine: repurposing initiatives - Ahsana Aqilah Ahmad,; Siti Mariam Abdul Rahman,; Irnie Azlin Zakaria,; Muhammad Syahiran Mohamad Tajolli,; Anis Syahirah Syaiful Azuan,; Fatin Batrisyia Jihat@Ahmad, (Penerbit Universiti Kebangsaan Malaysia, 2024)
A circular economy is an alternative to the traditional linear economy. The concept reduces waste by recovering resources at the end of a product’s life cycle and repurposing them to reduce environmental impact. The repurposing of machines is a model of production and consumption that involves re-pairing, refurbishing, and recycling to reduce waste. This project aims to improvise and repurpose existing mangosteen peeling machines into another suitable manufacturing process. The designed potato-cutting machine uses the existing conveyor system of a customised mangosteen peeling machine. The cutting mechanism incorporates safety and automation systems using through-beam infrared and capacitive proximity sensors. For the safety system, detecting objects within a range of 2.0 cm to the conveyor region indicates that the machine is unsafe to operate. The system will stop the machine and send audio and visual warnings to notify the users. Based on the trial runs the machine cuts the potato with approximately 1-tenth of the time needed in manual labour. The most significant benefit, however, is the overall savings in production costs, which are more than 85%. This is achieved as the machine re-purposes more than 50% of the components from the existing mangosteen peeling machine, such as sensors, control panel boxes, and PLC system. Consequently, this has helped minimise the overall cost of new equipment while encouraging a circular economy approach to engineering practices.